A Foucauldian Discourse Analysis of Regional Balance in the Financing of Higher Education in Uganda: The Uganda Students’ Higher Education Financing Policy Perspective - Kibuuka, Enock (East African Journal of Education Studies, 2022)
In Uganda, there have been historically glaring disparities in access to higher education, where the majority of the students that join universities come from good secondary schools, which are mostly afforded by rich individuals. This has created a situation of ‘inherited merit’, where students from particular backgrounds and regions dominate access to HE. Because children of the poor who cannot afford to go to good schools hardly access higher education, whilst many of the students who join higher education institutions (HEIs) fail to complete their study programmes due to the failure to meet the costs involved. The Ministry of Education and Sports 2012 introduced the Uganda Students’ Higher Education Financing Policy to address the problem of inequitable access to higher education. Thus, the third objective of the policy aims to ensure ‘regional balance’ in the provision of HE through awarding of student loans. Because there are strong intra-connections between policy and language, the language used in discourse plays a critical role in the way the term Regional balance was constructed in the policy. This paper performs a Foucauldian discourse analysis perspective of the policy with the overall aim of showing signs of power imbalance through the use of language and revealing the discourses used by elite actors to retain power and sustain existing regional imbalance in access to HE in Uganda. By approaching such regional balance as political discourse rather than a pure act of equity and social justice, the paper shows how power is implicated within the guise of regional balance. As such the paper contributes to a discursive understanding of regional balance in the provision of HE in Uganda, to an appreciation of the role of power relations embedded in policy rhetoric as a form of exemplary theatrical government, and to the politics of regional balance. The findings revealed that the term ‘regional balance’ is used as a sugar-coated camouflage to sustain and perpetuate the hegemony of the Western part of the country. The paper concludes by exposing the power relations embedded within the policy and highlights gaps between the rhetoric and practice of the policy in which people from the Western part of Uganda have benefited more from this financing policy at the expense of other students from other regions of the country